A mixed methods study of knee confidence and self-efficacy: perceptions of knee osteoarthritis patients from the good life with osteoarthritis in Denmark initiative - Ching, A.; Skou, S.T.; Thomas, S.A.; Batt, M.E.; Roos, E.M.; Edwards, K.L. (Elsevier, 2016)
Purpose: The Good Life with osteoArthritis in Denmark (GLA:D) Initiative is an evidence-based treatment programme for patients with knee and hip osteoarthritis (OA). It incorporates training physiotherapists to deliver care in accordance with the clinical guidelines by educating patients on their condition and by delivering supervised neuromuscular exercises to relieve pain and improve function. The importance of self-efficacy, and confidence in exercise, to exercise adherence has not been reported for the GLA:D population. In addition, worse knee confidence in people with knee OA is associated with higher pain and greater perceived knee instability. The aims of this study were to investigate the association between knee confidence and self-efficacy in patients with knee OA in the GLA:D registry; and to explore patients’ perception of their experiences with the GLA:D programme, and whether confidence and self-efficacy has a role to play in continuing with the GLA:D exercises in the long-term.